The Evolution of Transportation Concurrency and Urban Development Pattern in Miami-Dade County, Florida. (September 2014) - Kim, Jeongseob; Steiner, Ruth L.; Yang, Yizhao
Florida's transportation concurrency was introduced with much ambition to coordinate transportation infrastructure with development, but the lack of roadway capacity in urbanized areas and limited financial resource to invest in roads may have resulted in sprawl. Various policy responses to provide flexibility in the implementation of transportation concurrency, including Transportation Concurrency Exception Areas (TCEAs), have been introduced to address this concern. The adoption of the TCEA in Miami-Dade County was partially effective to reduce sprawl and increase urban infill, but the effectiveness may be undermined by locally discretionary implementation of transportation concurrency and inadequate traffic mitigation efforts.